Spatial Evaluation of Ambient Air Quality in Dobut Village, Manokwari - Marlia Mamede; Rizka Wahyuni Hatibie; Hasanuddin; Sari Agusliana; Ary Herlina Kurniati HM (Global Writing Academica Researching & Publishing, 2026)
Evaluation of ambient air quality conditions in Dobut Village, Manokwari, through a spatial approach based on 12 monitoring points. The parameters measured in this study consisted of PM₂.₅, NO₂, and SO₂ during the dry season. The data analysis used the Inverse Distance Weighting (IDW) interpolation method. The existing results show that most areas of Dobut Village have air quality in the